Pengembangan Modul Tematik Subtema Perkembangan Teknologi Transportasi Siswa Sekolah Dasar - La'bati Nur Aqrimna; Ida Putriani; Sripit Widiastuti (Musamus Journal of Primary Education, 2021)
Thematic learning in elementary school has obstacles in its implementation, one of which is related to the media. The results of the observation show that students need pictorial media. The purpose of this research is to develop learning media in the form of pictorial modules to support learning. The researchers used research development or Research and Development (R&D), according to Borg and Gall. The data collection technique used a questionnaire. Based on the results of material expert validation, it was 89%, linguist validation was 88%, and media expert validation was 84%. The results of the student readability questionnaire were 88%, and the teacher's readability questionnaire was 92%. The conclusion is the thematic module of the development of transportation technology for elementary students was developed suitable for use in learning.